The relationship between agility and dribbling skills among futsal players - Komang Ari Selin; Ni Komang Ayu Juni Antari; I Wayan Sugiritama; M. Widnyana (Physical Therapy Journal of Indonesia, 2024)
Background: Futsal is a popular sport in Indonesia, including Denpasar and Bali. This sport requires agility and high-skill techniques. Futsal requires players' skills in dribbling the ball well. Agility, the ability to move quickly and agilely, is an important physical component in futsal players, especially when dribbling. This study aimed to identify the relationship between the level of agility and dribbling skills in futsal players. Methods: The research design was observational analytic with a cross-sectional approach. The sampling technique used was consecutive sampling. The inclusion criteria for this study were futsal players aged 18-22. In contrast, the exclusion criteria were injuries in the leg region. The total number of respondents who participated in this study was 83 people. The research location is in Denpasar City, Bali. Data was collected from September until December 2023. Data were collected by measuring agility and dribbling skills. Agility was calculated using the Illinois agility test measurement instrument, while dribbling skills used the dribbling test measurement instrument. Results: Based on the Spearman rho non-parametric analysis test, the p-value = 0.000 (p < 0.05) and the correlation coefficient r = 0.642. Conclusion: There was a relationship between agility and dribbling skills in futsal players in Denpasar.